Regulation of glucose insulin metabolism using feedback linearization - Meriem Samai; Ghedjati Keltoum; Abdelaziz Mourad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin, or when the body is not able to effectively use the insulin it produces. Insulin is a hormone that regulates blood sugar levels, this regulation is done by the pancreas. When this organ is damaged, the patient will have to regulate its blood sugar level themselves. This task is really painful and we will have to resort to an artificial pancreas or we will have to design a regulator which stabilizes blood sugar at its basal value. Several controls have been developed and the objective of this paper is to use input output linearization technique to regulate blood glucose levels by injecting an adequate quantity of insulin. The glucose insulin metabolism is a non-linear system whose input is the quantity of insulin to be injected and the output is the blood glucose measured in the blood. Simulations examples are given to demonstrate the usefulness of the command developed.